Effect of linseed oil supplementation on performance and carcass traits of broiler chickens (Indian Journal of Animal Production and Management, 2024)
The experiment was conducted to study the effect of linseed oil supplementation on performance and  carcass traits of broiler chicken. For this purpose, 240 day-old commercial male broiler chicks were randomly  divided into four dietary groups with six replicates of ten birds each (4x6x10) and reared in deep litter up  to 35 days of age following standard management and vaccination schedule. The birds were offered with  corn-soya based broiler pre-starter (0-11 days), starter (12-21 days) and finisher (22-35 days) diets. The  control diet (T1) was prepared with soybean oil and diets for remaining treatment groups (T2- T4) were  formulated by replacing soybean oil with different levels of linseed oil. The experimental design consisted  of T1 - Control diet with 3% soybean oil, T2 – control diet with 2% soybean oil and 1% linseed oil, T3 - control  diet with 1% soybean oil and 2% linseed oil and T4 - control diet with 3% linseed oil. The performance of  broiler chicken was evaluated in terms of weekly body weight gain (WBWG) and feed consumption (FC) as  influenced by the supplementation of various levels of linseed oil. At the end of experiment (35th day) two  birds from each replicate were randomly selected for estimating slaughter parameters. Feed consumption  was unaffected due to different dietary treatments. Significant (P
Keywords: Broiler chicken; Linseed oil; N- 3 fatty acids; Performance